2019
DOI: 10.1002/ams2.446
|View full text |Cite
|
Sign up to set email alerts
|

“Impact of timing of polymyxin B‐immobilized fiber column direct hemoperfusion on outcome in patients with septic shock: a single‐center observational study”

Abstract: The effect of polymyxin B-immobilized fiber column direct hemoperfusion (PMX-DHP) is controversial. The present study investigates whether outcome in septic shock patients is affected by the time until PMX-DHP initiation and the location of the infection site (intra-or extra-abdominal infection (IAI/EAI)]. Methods: This retrospective observational study included patients receiving PMX-DHP for septic shock but excluded those treated after cardiac surgery or cardiac arrest. Based on the median and/or quartile ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…A previous study reported that early PMX‐DHP had better outcomes in patients with intra‐abdominal infection, not in extra‐abdominal infection 12 . However, in our study there was no difference in therapeutic effect of early PMX‐DHP (≤12 hours) between intra‐abdominal (N = 29) and extra‐abdominal (N = 18) infection site (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…A previous study reported that early PMX‐DHP had better outcomes in patients with intra‐abdominal infection, not in extra‐abdominal infection 12 . However, in our study there was no difference in therapeutic effect of early PMX‐DHP (≤12 hours) between intra‐abdominal (N = 29) and extra‐abdominal (N = 18) infection site (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
“…In the past, there were two reports that the early initiation of PMX‐DHP for septic shock results in better outcomes 11,12 . Tanaka et al reported that early initiation of PMX‐DHP was especially effective in the case of septic shock with intra‐abdominal infection in which presence of hyperendotoxemia was expected 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, starting PMX‐DHP early may be associated with favorable outcome. Indeed, the timing of PMX‐DHP initiation is reported to be an important factor for survival in patients with sepsis . We recommend that PMX‐DHP be performed as soon as possible for bacterial meningitis with impaired consciousness (GCS score < 12).…”
Section: Discussionmentioning
confidence: 99%